Music in Euripides' Medea - Thomas, Oliver (Oxford University Press, 2018)
Argues for the plausibility of Athenaeus' evidence that Euripides' Medea contained an innovative treatment of melody, and discusses how this may have interacted with what the characters within the play say about musical innovations.